Front Cover. Issue 3 (11th February 2020) - Wei, Peng; Demaeght, Peter; De Schutter, Kristof; Grigoraki, Linda; Labropoulou, Vassiliki; Riga, Maria; Vontas, John; Nauen, Ralf; Dermauw, Wannes; Van Leeuwen, Thomas
Abstract : The front cover image is based on the Research Article Overexpression of an alternative allele of carboxyl/choline esterase 4 (CCE04) of Tetranychus urticae is associated with high levels of resistance to the keto‐enol acaricide spirodiclofen by Peng Wei et al., https://doi.org/10.1002/ps.5627 . Abstract : The front cover image is based on the Research Article Overexpression of an alternative allele of carboxyl/choline esterase 4 (CCE04) of Tetranychus urticae is associated with high levels of resistance to the keto‐enol acaricide spirodiclofen by Peng Wei et al., https://doi.org/10.1002/ps.5627 .